EDUCATORS IN OVERCOMING CHILD TEMPER TANTRUMS AT ISLAMIC KINDERGARTEN TAZKIA, SUNGGAL DISTRICT, DELI SERDANG REGENCY - Widya, Rika; Rozana, Salma; Ependi, Rustam; Zahrita, Zahrita (Proceeding International Seminar of Islamic Studies, 2024)
Early childhood is a period where children's development can optimally grow, both in the social-emotional aspect and other aspects. Therefore, efforts to address children experiencing temper tantrums are crucial to ensure that children's development can progress optimally. This research employs a qualitative research method with a psychological approach. The subjects of this study are educators and children experiencing tantrums at Tazkia Islamic Kindergarten, Sunggal District, Deli Serdang Regency. Data collection techniques used include observation, documentation, and interviews. For data analysis, the researcher uses the data analysis technique from Miles and Huberman. In the final stage, the validity of the obtained data will be tested using triangulation techniques, both source and method. The results of this research are expected to provide deeper insights into ways to overcome temper tantrums in early childhood at Tazkia Islamic Kindergarten, Sunggal District, Deli Serdang Regency. Additionally, this study will also produce recommendations for educators in applying emotional-based approaches to managing temper tantrums. Thus, this research has the potential to contribute positively towards efforts to manage early childhood temper tantrums and encourage the formation of early childhood character.